Financial Performance Of Semarang City KONI In Fiscal Year 2018–2023 - Annisa Raissa Nathania; Widhian Hardiyanti (SEAN Institute, 2024)
This study aims to analyze the financial performance of KONI Semarang City in 2018 to 2023 whether the financial performance of KONI Semarang City is effective in using the budget in every activity that has been planned in the RKA prepared in that fiscal year so that it can be efficient in minimizing the remaining budget that cannot be absorbed. The analysis method used by the researcher is description analysis by using quantitative data from KONI Semarang City directly and supported by secondary data taken from several related journals available on the journal's website. In the end, the analysis shows that KONI Semarang City has effective and efficient financial performance because it can maximize the absorption of budget realization and minimize the remaining budget in the implementation of activities during the current fiscal year.